Critical role of the neural pathway from the intermediate medial mesopallium to the intermediate hyperpallium apicale in filial imprinting of domestic chicks (Gallus gallus domesticus). (12th November 2015) - Aoki, N.; Yamaguchi, S.; Kitajima, T.; Takehara, A.; Katagiri-Nakagawa, S.; Matsui, R.; Watanabe, D.; Matsushima, T.; Homma, K.J.
Highlights: We investigated the neural circuits downstream from the IMM for imprinting. The IMHA region is critical not only for imprinting acquisition, but also for recall. The IMHA region works for imprinting downstream from T3 action in the IMM. We revealed the neural connections from the IMM to the IMHA. Abstract: Filial imprinting in precocial birds is a useful model for studying early learning and cognitive development, as it is characterized by a well-defined sensitive or critical period. We recently showed that the thyroid hormone 3, 5, 3′-triiodothyronine (T3 ) determines the onset of the sensitive period. Moreover, exogenous injection of T3 into the intermediate medial mesopallium (IMM) region (analogous to the associative cortex in mammals) enables imprinting even on post-hatch day 4 or 6 when the sensitive period has been terminated. However, the neural mechanisms downstream from T3 action in the IMM region remain elusive. Here, we analyzed the functional involvement of the intermediate hyperpallium apicale (IMHA) in T3 action. Bilateral excitotoxic ablation of the IMHA prevented imprinting in newly hatched chicks, and also suppressed the recovery of the sensitive period by systemic intra-venous or localized intra-IMM injection of T3 in day-4 chicks. In contrast to the effect in the IMM, direct injection of T3 into the IMHA did not enable imprinting in day-4 chicks. Moreover, bilateral ablation of IMHA after imprinting training impaired recall. These results suggest that the IMHA is critical for memory acquisition downstream following T3 action in the IMM and further, that it receives and retains information stored in the IMM for recall. Furthermore, both an avian adeno-associated viral construct containing an anterograde tracer (wheat-germ agglutinin) and a retrograde tracer (cholera toxin subunit B) revealed neural connections from the IMM to the IMHA. Taken together, our findings suggest that hierarchical processes from the primary area (IMM) to the secondary area (IMHA) are required for imprinting.